Station Eleven [compact disc, unabridged] : a novel - Mandel, Emily St. John, 1979- (Random House Audio, 2014)
One snowy night Arthur Leander, a famous actor, has a heart attack onstage during a production. Jeevan Chaudhary, is in the audience and leaps to his aid. A child actress named Kirsten Raymonde watches in horror as Jeevan performs CPR, pumping Arthur's chest as the curtain drops, but Arthur is dead. That same night, as Jeevan walks home from the theater, a terrible flu begins to spread. Hospitals are flooded and Jeevan and his brother barricade themselves inside as life disintegrates outside.